2017
DOI: 10.4162/nrp.2017.11.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of dietary reference intake predictive equation for estimated energy requirements in female tennis athletes and non-athlete college students: comparison with the doubly labeled water method

Abstract: BACKGROUND/OBJECTIVESThe purpose of this study was to assess the accuracy of a dietary reference intake (DRI) predictive equation for estimated energy requirements (EER) in female college tennis athletes and non-athlete students using doubly labeled water (DLW) as a reference method.MATERIALS/METHODSFifteen female college students, including eight tennis athletes and seven non-athlete subjects (aged between 19 to 24 years), were involved in the study. Subjects' total energy expenditure (TEE) was measured by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…The study showed that athletes' EE averaged 2,501 kcal/day, with no significant differences between tennis (2,557 kcal/day) and soccer (2,485 kcal/day) players. The EE values of this study were similar to those in the previous studies that have shown daily EE values to be 2,780kcal among female tennis players (Ndahimana, et al, 2017) and between 2,274kcal and 2,925kcal among soccer players (Mara, et al, 2015;Santos, et al, 2016). It is noteworthy that Ndahimana et al (2017) study did not report the expertise level of the tennis players or how many practices or games the sample had during their study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study showed that athletes' EE averaged 2,501 kcal/day, with no significant differences between tennis (2,557 kcal/day) and soccer (2,485 kcal/day) players. The EE values of this study were similar to those in the previous studies that have shown daily EE values to be 2,780kcal among female tennis players (Ndahimana, et al, 2017) and between 2,274kcal and 2,925kcal among soccer players (Mara, et al, 2015;Santos, et al, 2016). It is noteworthy that Ndahimana et al (2017) study did not report the expertise level of the tennis players or how many practices or games the sample had during their study.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that elite female tennis players expend on average 443±79 and 664±118kcal per 60min and 90min match, respectively (Hornery, Farrow, Mujika, & Young, 2007;Martin, et al, 2011;Mendez-Villanueva, Fernandez-Fernandez, Bishop, Fernandez-Garcia, & Terrados, 2007;Ranchordas, et al, 2013), whereas female soccer players expend estimated 966kcal during a 90min game (Mara, et al, 2015). Although a South Korean study (N=8; 19-24-year-old) showed EE of female college players to be daily 2,780±429kcal (Ndahimana, et al, 2017), the study did not report the expertise level of the players or the structure of their week (how many practices or matches they played). On the other hand, it has been shown that professional female soccer players' energy intake during preseason training (N=21; 3 hours of training daily) is on average 2,701±214kcal (Santos, Silveira, & Cesar, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Studies on the measurement of TEE by applying the DLW method have been conducted in various countries [ 32 33 34 35 36 ], though the number of studies is limited. Among these, we have compared our results with two studies conducted in Japan, a population that has similar ethnic characteristics to those of Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to measure the EE of athletes during their daily life. In general, most athletes have higher EEs, reflecting their high-level physical activities and body composition ( Ndahimana et al., 2017 ). Accordingly, compared with non-athletes, athletes are in greater nutritional demand ( Ranchordas et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes have well-developed muscular systems and even larger organs (such as the liver, heart, and kidneys) ( Miyauchi et al., 2013 ). Since more muscles consume more energy according to the oxygen uptake ( Armstrong & McManus, 2011 ; Farinatti & Castinheiras Neto, 2011 ), athletes have a higher resting metabolic rate (RMR) and total energy expenditure (TEE) than non-athletes ( Ribeyre et al., 2000 ; Kim et al., 2015 ; Ndahimana et al., 2017 ). However, despite applications of wearable devices for measuring activity load ( Ritchie et al., 2016 ; Stiles et al., 2018 ) and estimate EE ( Yang, Gerhard & Barden, 2015 ; Larsen et al., 2017 ; Sirichana et al., 2017 ), variations between athletes and non-athletes are rarely considered.…”
Section: Introductionmentioning
confidence: 99%